Gene Methylation as a Potential Epigenetic Marker for Ovarian Cancer - Aysegul Gonc; Ozge Sukruoglu Erdogan; Seda Kilic Erciyas; Betul Celik Demirbas; Ahmet Dinc; Ozge Pasin; Pınar Saip; Hulya Yazici; Seref Bugra Tuncer (Clinical Medicine Insights: Oncology)
Background: Ovarian cancer (OC) is a significant health problem often diagnosed at an advanced stage due to the lack of early symptoms and effective screening methods. This study aimed to explore the role of CYB5R4 gene methylation as a potential biomarker for ovarian cancer. Methods: DNA isolation was performed in the blood samples of 387 ovarian cancer patients, 50 individuals with benign ovarian diseases, and 100 healthy controls. The CYB5R4 gene methylation status was evaluated using the Methyl-Specific Restriction Enzymes (MSREs) technique and methylation levels were compared between the groups. Results: Ovarian cancer patients exhibited the highest mean methylation percentage (9.45%) and median (6.23%), followed by healthy controls with a mean of 9.14% and a median value of 4.47%. Statistical analysis showed significant differences in methylation levels ( P  = .041), suggesting that CYB5R4 methylation may be associated with ovarian cancer progression. Conclusion: The CYB5R4 gene methylation may serve as a potential biomarker for ovarian cancer, particularly in distinguishing between malignant and benign conditions. Further research is needed to validate these findings and explore the clinical utility of CYB5R4 methylation in ovarian cancer management.